Dramatic change in a young woman's perception of her diabetes and remarkable reduction in HbA1c after an individual course of Guided Self-Determination. (6th July 2015) - Zoffmann, Vibeke; Prip, Anne; Christiansen, Anette Wendelboe
Abstract : A 24-year-old woman with type 1 diabetes participated in a randomised controlled trial proving effectiveness of a flexible Guided Self-Determination (GSD) intervention. She had for 10 years been living with a complex situation of eating disorder, poor glycaemic control, non-attendance and psychosocial distress. She managed to change her perception of diabetes dramatically and improved her glycaemic control. Considering the complexity of her case, we explored how she achieved these changes. A GSD-trained nurse delivered the intervention, which involves reflection sheets and advanced professional communication. Glycated hemoglobin was reported in the patient's record and an interview conducted by external interviewers was analysed thematically, indicating that a four-stage process of empowerment had taken place: 'focusing on life prior to numbers', 'unpacking a heavy burden', 'breaking out of isolation through communication' and 'finding strength within oneself'. The article emphasises that GSD works by breaking isolation through communication as an appropriate way to achieve good diabetes control.